Vocal tract discomfort in caregivers for the elderly during an interval of the COVID-19 pandemic. (3rd July 2022) - Gantner, Sophia; Deitmerg, Ursula; Schuster, Maria
Abstract: Background: During the coronavirus disease 2019 (COVID-19) pandemic, professional caregivers caring for the elderly may experience more vocal tract problems in addition to regular high vocal demands while wearing face masks/coverings. Methods and participants: Vocal tract discomfort (VTD) was assessed in 64 caregivers in one home for the elderly (64% participation rate) in June 2020 using the German version of the VTD scale. Results: More than one-half of the participating caregivers experienced VTD, described mostly as dryness, irritability, and tightness. Approximately, 80% reported that sensations were not perceived before enhanced infection prevention standards were implemented. Conclusions: Among caregivers caring for the elderly during the COVID-19 pandemic, special care should be focused on the voice and vocal tract well-being.